“Dividing the Wheat from the Chaff” : How to Get at the True Picture of Entrepreneurship Behind Misleading Statistics – Lessons from Ukraine’s Example - Kuzmyn, Yuriy; Blanc, Florentin (World Bank, Washington, DC, 2012)
In recent years, a growing emphasis has been put on results measurement and also on using hard data to evaluate and steer policy. Given the significant efforts in many countries to simplify business entry, this has led to an interest in using data from business registries to compare the number of businesses and the dynamics of entrepreneurship across countries. Significant differences between the officially reported figures on entrepreneurship (which get reflected in international indices) and the real situation mean that the design of reform interventions and solutions can be seriously misguided. The government as well as the donor community, and not least International Finance Corporation (IFC), need to take this into account when designing programs aimed at fostering private sector development. The World Bank Group Entrepreneurship Database (WBG ED), a joint effort led by the IFC Small and Medium Enterprise (SME) Department and the World Bank Development Research Group, is known as the most comprehensive dataset on cross-country firm entry data available today. It includes cross-country, time-series data on the number of total and newly registered businesses and was collected directly from the registrars of companies via questionnaires. On the other hand, the IFC Ukraine business enabling environment project has for several years been collecting data on the number of registered and active companies in order to structure the sample for business environment surveys and to provide basic data on the evolution of entrepreneurship in the country.